IMPLEMENTASI LEBAH GALO-GALO SEBAGAI POLINATOR PADA LAHAN PERTANIAN MENGGUNAKAN KOTAK HIVE DI SUNGKAI KELURAHAN LAMBUNG BUKIK KECAMATAN PAUH KOTA PADANG - Rusdimansyah, Rusdimansyah; Hidrayani, Hidrayani; Ikhsan, Zahlul (Jurnal Hilirisasi IPTEKS, 2022)
Pollination is an essential part of increasing crop production. One insect that acts as a pollinator on plants is the Galo-galo bee. Stingless bee cultivation can help in the pollination process and serve as a producer of pure honey, which also has the potential to increase farmers' income. This activity aims to enable partner groups at the Andalas University campus to cultivate stingless bees on agricultural land. The methods used in this service are counseling, mentoring, training, and piloting. Extension materials were carried out to increase farmers' knowledge about the potential of stingless bees, the introduction of natural colony trapping methods, and bee food sources. The service team has brought several Galo-galo bee colonies that farmer groups in Sungkai will maintain. By bringing the colony bees, farmers are given other material, namely how to transfer the colony to the cultivation box, install the honey box, and harvest. The results of this activity are as follows: 1) Increased knowledge, interest, and skills of partners in raising Galo-galo, which is integrated with agriculture. 2) Partner has a new business unit in the form of Galo-galo cattle. 3) Partners have a new commodity produced, namely Galo-galo honey. 4) Partners know and can cultivate bee food plants. This activity ran smoothly, and the target of the movement was achieved well. Farmers participating in the service have cultivated stingless bees on managed agricultural land.